Identifikasi Perilaku Perjalanan Melalui Metode Critical Path Method (CPM) - Lulu Mari Fitria; Mutiasari Kurnia Devi; Muhammad Sani Roychansyah; Yori Herwangi; Siti Nurjanah (Diponegoro University, 2020)
Mobilization in urban areas has increased every year along with the population growth and urban's development. Travel behaviors of the population in urban areas can be classified based on their travel characteristics. The identification of communities' travel behavior of Yogyakarta is based on the origin - destination and length of trip based on age characteristics. It will effects the travel patterns in the urban environment through spatial mapping. The method used in this research is critical path method. Critical Path Method (CPM) is used to determine the optimum path taken by the community based on its duration, which in this study CPM is used to determine the average travel of the community based on age groups when viewed from distance, length of trip and the number of daily trips. Based on the analysis, it shows that the average age of 15-22 years and 31-37 years have the highest travel time, which is about 9 hours and the average age of 23-30 years traveled the longest by 12.5 km. The average mobilization of travel behaviors in KPY is to the urbancenter of Yogyakarta. The KPY urban form does not have a compact form.